Sequencing and characterisation of rearrangements in three S. pastorianus strains reveals the presence of chimeric genes and gives evidence of breakpoint reuse. - Sarah K Hewitt; Ian J Donaldson; Simon C Lovell; Daniela Delneri (PLoS ONE)
Gross chromosomal rearrangements have the potential to be evolutionarily advantageous to an adapting organism. The generation of a hybrid species increases opportunity for recombination by bringing together two homologous genomes. We sought to define the location of genomic rearrangements in three strains of Saccharomyces pastorianus, a natural lager-brewing yeast hybrid of Saccharomyces cerevisiae and Saccharomyces eubayanus, using whole genome shotgun sequencing. Each strain of S. pastorianus has lost species-specific portions of its genome and has undergone extensive recombination, producing chimeric chromosomes. We predicted 30 breakpoints that we confirmed at the single nucleotide level by designing species-specific primers that flank each breakpoint, and then sequencing the PCR product. These rearrangements are the result of recombination between areas of homology between the two subgenomes, rather than repetitive elements such as transposons or tRNAs. Interestingly, 28/30 S. cerevisiae-S. eubayanus recombination breakpoints are located within genic regions, generating chimeric genes. Furthermore we show evidence for the reuse of two breakpoints, located in HSP82 and KEM1, in strains of proposed independent origin.